Health Care Needs of Communitydwelling Older Adults - Krueger, Paul (Can J Public Health, 2000)
Objective: To identify, assess, and rank the importance of health care needs of communitydwelling older adults. Method: A structured telephone interview with 107 respondents (physicians, direct service providers and administrators) about the importance of a list of 31 health care needs of older adults. Respondents also identified the single most important health issue facing local older adults now and in the next 5 to 10 years. Results: The five most important health care needs, in descending order, are: care-giver support services, community long-term care services, services for people with dementia/Alzheimer’s disease, palliative/end-oflife care, and services for cancer patients and their families. Community long-term care services were identified as the single most important health issue both now and in the next 5 to 10 years. Conclusion: The study findings should be of value to health and social service researchers, planners, providers and administrators regarding the needs of community-dwelling older adults.